2017
DOI: 10.1021/acs.jpcc.7b07155
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Observation of the Plasmonic Effect in Photochromic Ag Nanoparticle Filled Mesoporous TiO2 Films

Abstract: We report photoelectrochemical measurements from mesoporous titanium dioxide filled with silver nanoparticles under illumination. A 200 mV potential switch of silver ion reduction is observed, depending on light wavelength. An easier reduction of silver in the presence of light is linked to plasmon induced charge separation (PICS). SEM and TEM analysis before and after photoelectrochemistry have also shown an electrochemical Ostwald ripening during continuous visible irradiation, with a growth of silver partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…All the above experimental data clearly suggest that the electrophotochromism of the Ag-TiO2 composite is due to oxidation/reduction of the Ag nanoparticles, which forms a thin layer of Ag2O on the metallic core, forming core/shell nanoparticles; the core is metallic while the outer shell is semiconducting, where the peaks agree well with those found by Kuzma et al [46]. In fact, it is suggested that the oxide thickness is about 1.5 nm when the composite absorbs at the 440 nm peak and at most 0.5 nm while the composite exhibits a peak at 413 nm.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…All the above experimental data clearly suggest that the electrophotochromism of the Ag-TiO2 composite is due to oxidation/reduction of the Ag nanoparticles, which forms a thin layer of Ag2O on the metallic core, forming core/shell nanoparticles; the core is metallic while the outer shell is semiconducting, where the peaks agree well with those found by Kuzma et al [46]. In fact, it is suggested that the oxide thickness is about 1.5 nm when the composite absorbs at the 440 nm peak and at most 0.5 nm while the composite exhibits a peak at 413 nm.…”
Section: Discussionsupporting
confidence: 86%
“…There is also the possibility that some of the non-reduced silver ions (Ag + ) could be adsorbed on the hydroxylated TiO2 surface according to the following reaction, as suggested by other authors also in the past: Ag + + TiO2 − → Ti-O-Ag + H + [45]. The plasmon resonance in the Ag-TiO2 thin films strongly depends on the crystalline phase and dielectric constant of the TiO2 matrix [46]. In theory, the SPR peak wavelength increases with increasing dielectric constant of the matrix and depends on the refractive index.…”
Section: Agnp 12 Nmmentioning
confidence: 98%
See 2 more Smart Citations
“…31,32 We initially studied the photoelectrochemical properties of a TiO electro-reduction potential can be modulated by light irradiation and that silver repartition within the mesoporous matrix is modified. 33 In this work, we synthesized silver NPs embedded in mesoporous TiO 2 films and characterized them through scanning electron microscopy (SEM), UV−visible absorption, and photoelectrochemistry at different wavelengths. The present study describes the specific effect of wavelength on the silver ions reduction potential and probes the chemical bonding between the silver NPs and titania matrix.…”
Section: ■ Introductionmentioning
confidence: 99%